PENDAFTARAN AKTA JUAL BELI YANG MELEBIHI JANGKA WAKTU PENDAFTARAN TANAH DI KANTOR AGRARIA DAN TATA RUANG/BADAN PERTANAHAN NASIONAL KOTA SEMARANG - Kusmaryanto Kusmaryanto; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
Implementation Land registration in society is now the task of the State. Land registration is carried out by the government for the benefit of the people, as an effort to provide legal certainty in the field of land. The Land Registration is carried out by the Land Office, and in carrying out the tasks the Land Office is assisted by The Land Deed Official, to carry out the activities set forth in PP 24/1997.The formulation of the problem in this research are: 1) How is the regulation of the registration of the Deed of Sale and Purchase exceeding the period of registration of land for the realization of legal certainty ?; 2) What are the obstacles faced by the Land Deed Officer in relation to the deed of sale and purchase that exceeds the period of land registration, which is shown for the realization of legal certainty and how is the solution to the settlement?This research method using research approach that is juridical normative. The specifications of this study were descriptively analyzed. Methods of data collection in this study, can be obtained by library research.The result of the research says that 1. The legal arrangement of registration of Deed of Sale and Purchase exceeding the time period specified for the realization of legal certainty is where if the registration of sale and purchase certificate exceeds 7 days then it is requested more clearly to the local Land Office. 2. The obstacles faced by the Land Deed Authority in relation to the deed of sale and purchase that exceeds the period of land registration such as the lack of public awareness, the bad image of the National Land Agency and the rights base is different from the field data. To overcome these obstacles then the National Land Agency made a program such as doing counseling to the public and through the PRONA program.The conclusion of the research results suggests that the legal arrangement of registration of Sale and Purchase Deed beyond the time period specified for the realization of legal certainty is where if the registration of the deed of sale and purchase exceeds 7 days then applied more clearly to the local Land Office. Although the submission of the deed of sale and purchase of land to the Land Office as practiced by most of the Land Deed Officials is not in accordance with the applicable laws but does not result in the cancellation of the land and there is no legal provision stating that With the delay of submission of the deed of sale and purchase of the land makes the relevant deed null and void. Keywords: Deed of Sale and Purchase, Land Registration